2022
DOI: 10.1021/acsomega.2c01195
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Optimization of Charge Transport Properties in a Triple-Cation Perovskite Layer and Triple-Cation Perovskite/Spiro-OMeTAD Interface by Dual Passivation

Abstract: Molecular engineering of additives is a highly effective method to increase the efficiency of perovskite solar cells by reducing trap states and charge carrier barriers in bulk and on the thin film surface. In particular, the elimination of undercoordinated lead species that act as the nonradiative charge recombination center or contain defects that may limit interfacial charge transfer is critical for producing a highly efficient triple-cation perovskite solar cell. Here, 2-iodoacetamide (2I-Ac), 2-bromoaceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 86 publications
(159 reference statements)
0
1
0
Order By: Relevance
“…Various approaches have been utilized to address the thermal degradation issues in halide perovskite materials. These include opting for thermally stable halide perovskite materials such as FAPbI 3 , CsPbI 3 , and so on, [27][28][29] incorporating additives, [30][31][32][33][34][35][36] employing passivation layers, [37,38] fine-tuning of the material composition, and so on. [39][40][41] It has been reported that FAPbI 3 -based PSCs are thermally stable at 85 °C temperature and it maintained 85% of its initial PCE up to 400 h. [42,43] However, the challenges that FAPbI 3 faces are that at room temperature it undergoes phase transition from photoactive black perovskite phase to photoinactive hexagonal nonperovskite phase.…”
mentioning
confidence: 99%
“…Various approaches have been utilized to address the thermal degradation issues in halide perovskite materials. These include opting for thermally stable halide perovskite materials such as FAPbI 3 , CsPbI 3 , and so on, [27][28][29] incorporating additives, [30][31][32][33][34][35][36] employing passivation layers, [37,38] fine-tuning of the material composition, and so on. [39][40][41] It has been reported that FAPbI 3 -based PSCs are thermally stable at 85 °C temperature and it maintained 85% of its initial PCE up to 400 h. [42,43] However, the challenges that FAPbI 3 faces are that at room temperature it undergoes phase transition from photoactive black perovskite phase to photoinactive hexagonal nonperovskite phase.…”
mentioning
confidence: 99%